Osteoarthritis and other long-term health conditions in former elite cricketers. Issue 6 (June 2018) - Jones, Mary E.; Davies, Madeleine A.M.; Leyland, Kirsten M.; Delmestri, Antonella; Porter, Angus; Ratcliffe, Jason; Peirce, Nick; Newton, Julia L.; Arden, Nigel K.
Abstract: Objectives: This study aimed to describe the prevalence and risk of chronic conditions in former elite cricketers compared to a normal population, and describe wellbeing in former elite cricketers. Design: Cross-sectional study. Methods: Former elite cricketers, recruited from the Professional Cricketers' Association, completed a self-report cross-sectional questionnaire. The English Longitudinal Study of Ageing (ELSA) served as the normal population. The prevalence of self-reported, GP-diagnosed conditions (heart problems, hypertension, stroke, diabetes, asthma, dementia, osteoarthritis (OA), total hip replacement (THR), total knee replacement (TKR), anxiety, depression) were reported for both population samples. Standardised morbidity ratios (SMRs) compared chronic conditions in sex-, age- and BMI-matched former cricketers (n = 113) and normal population (n = 4496). Results: Heart problems were reported by 13.3% of former cricketers, significantly lower than the normal population, SMR 0.55 (0.33–0.91). Former cricketers reported 31.9% hypertension, 1.8% stroke, 6.2% diabetes, 15.0% asthma, and no dementia, none significantly different to the normal population. OA, THR, and TKR were reported by 51.3%, 14.7% and 10.7% of former cricketers, respectively, significantly higher than the normal population, SMRs 3.64 (2.81–4.71), 3.99 (2.21–7.20) and 3.84 (1.92–7.68). Anxiety and depression were reported by 12.4% and 8.8% of former cricketers, respectively, SMRs 3.95 (2.34–6.67) and 2.22 (1.20–4.14). 97% of former cricketers reflected they would undertake their cricket career again, 98% agreed that cricket enriched their lives. Conclusions: Heart problems were significantly lower, while OA, THR, TKR, anxiety, and depression were significantly higher in the former cricketers compared to the normal population (ELSA). Most former cricketers reflected positively on their career.